Pemanfaatan Media Realia untuk Meningkatkan Aktivitas dan Prestasi Menulis Pantun pada Siswa Kelas VI SD Negeri 2 Sawah Lama Bandar Lampung Tahun Pelajaran 2019/2020 - Sukinah Sukinah (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2022)
The purpose of this study was to describe the increase in Pantun learning activities and achievements using environmental media in Class VI students of State Elementary School 2 Sawah Lama in the 2019/2020 academic year. The method used in this research is Classroom Action Research (CAR) through 3 cycles and 3 meetings in each cycle. The research subjects were students of Class VI Semester 1 of SDN 2 Sawah Lama Bandar Lampung for the 2019/2020 academic year. totaling 30 students. The data were obtained from the notes of the observer's observation sheet on the learning process planned by the researcher, the observation sheet of learning activities and the test sheet to determine learning achievement and the observer's observation of the learning carried out by the researcher. Based on the findings and results of the discussion, it was found that the use of environmental media could increase the activity and achievement of learning to write poetry in Class VI semester 1 SDN 2 Sawah Lama Bandar Lampung.